Q. 175.0( 3 Votes )

If f: R <span lan

Answer :

We have f: R (–1, 1) and


Given that f-1 exists.


Let y ϵ (–1, 1) such that f(x) = y





102x – 1 = y (102x + 1)


102x – 1 = 102xy + y


102x – 102xy = 1 + y


102x (1 – y) = 1 + y



Taking log10 on both sides, we get






We have f(x) = y x = f-1(y)


But, we found f(x) = y


Hence,


Thus,


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

| Let * be a binaMathematics - Board Papers

Find the idMathematics - Board Papers

Let f : A Mathematics - Exemplar

Show that the binMathematics - Board Papers

Determine whetherRD Sharma - Volume 1

Fill in theMathematics - Exemplar